In vitro antifungal susceptibility patterns of Trichophyton benhamiae complex isolates from diverse origin - Shamsizadeh, Forough; Ansari, Saham; Zarei Mahmoudabadi, Ali; Hubka, Vít; Čmoková, Adéla; Guillot, Jacques; Rafiei, Abdollah; Zomorodian, Kamiar; Nouripour-Sisakht, Sadegh; Diba, Kambiz; Mohammadi, Tooba; Zarrinfar, Hossein; et al. (Mycoses, 2021)
BACKGROUND: Species from the Trichophyton benhamiae complex are mostly zoophilic dermatophytes which cause inflammatory dermatophytosis in animals and humans worldwide. OBJECTIVES: This study was purposed to (a) to identify 169 reference and clinical dermatophyte strains from the T benhamiae complex species by molecular method and adhering to the newest taxonomy in the complex (b) to evaluate the in vitro antifungal susceptibility profile of these strains against eight common and new antifungal agents that may be used for the treatment of dermatophytosis. METHODS: All isolates, mainly originated from Europe but also from Iran, Japan and USA, were subjected to ITS-rDNA sequencing. The in vitro antifungal susceptibility profiles of eight common and new antifungal drugs against the isolates were determined by CLSI M38-A2 protocol and according to microdilution method. RESULTS: Based on the ITS-rDNA sequencing, T benhamiae was the dominant species (n = 102), followed by T europaeum (n = 29), T erinacei (n = 23), T japonicum (n = 10), Trichophyton sp (n = 4) and T eriotrephon (n = 1). MIC ranges across all isolates were as follows: luliconazole: 0.0002-0.002 µg/ml, terbinafine: 0.008-0.125 µg/ml, efinaconazole: 0.008-0.125 µg/ml, ciclopirox olamine: 0.03-0.5 µg/ml, itraconazole: 0.06-2 µg/ml, griseofulvin: 0.25-4 µg/ml, amorolfine hydrochloride: 0.125-4 µg/ml and tavaborole: 1-16 µg/ml. CONCLUSION: Luliconazole, efinaconazole and terbinafine were the most potent antifungals against T benhamiae complex isolates, regardless of the geographic locations where strains were isolated. These data might help dermatologists to develop effective therapies for successful treatment of infections due to T benhamiae complex species.
Keywords: Spojené státy americké; Humans; antifungální látky; Japonsko; Iran; lidé; zoonózy; zvířata; Europe; T benhamiae; United States; Japan; Írán; antifungal susceptibility; Arthrodermataceae; Antifungal Agents; T erinacei; Zoonoses; tinea; Tinea; Animals; Evropa